Bone Geometry, Volumetric Density, Microarchitecture, and Estimated Bone Strength Assessed by HR‐pQCT in Klinefelter Syndrome. (November 2014) - Shanbhogue, Vikram V; Hansen, Stinus; Jørgensen, Niklas Rye; Brixen, Kim; Gravholt, Claus H
ABSTRACT Although the expected skeletal manifestations of testosterone deficiency in Klinefelter's syndrome (KS) are osteopenia and osteoporosis, the structural basis for this is unclear. The aim of this study was to assess bone geometry, volumetric bone mineral density (vBMD), microarchitecture, and estimated bone strength using high‐resolution peripheral quantitative computed tomography (HR‐pQCT) in patients with KS. Thirty‐one patients with KS confirmed by lymphocyte chromosome karyotyping aged 35.8 ± 8.2 years were recruited consecutively from a KS outpatient clinic and matched with respect to age and height with 31 healthy subjects aged 35.9 ± 8.2 years. Dual‐energy X‐ray absorptiometry (DXA) and HR‐pQCT were performed in all participants, and blood samples were analyzed for hormonal status and bone biomarkers in KS patients. Twenty‐one KS patients were on long‐term testosterone‐replacement therapy. In weight‐adjusted models, HR‐pQCT revealed a significantly lower cortical area (p < 0.01), total and trabecular vBMD (p = 0.02 and p = 0.04), trabecular bone volume fraction (p = 0.04), trabecular number (p = 0.05), and estimates of bone strength, whereas trabecular spacing was higher (p = 0.03) at the tibia in KS patients. In addition, cortical thickness was significantly reduced, both at the radius and tibia (both p < 0.01). There were no significant differences in indices of bone structure, estimated bone strength, or bone biomarkers in KS patients with and without testosterone therapy. This study showed that KS patients had lower total vBMD and a compromised trabecular compartment with a reduced trabecular density and bone volume fraction at the tibia. The compromised trabecular network integrity attributable to a lower trabecular number with relative preservation of trabecular thickness is similar to the picture found in women with aging. KS patients also displayed a reduced cortical area and thickness at the tibia, which in combination with the trabecular deficits, compromised estimated bone strength at this site. © 2014 American Society for Bone and Mineral Research.